EDUCATION IN THE HUMANITIES AND THE DEMOCRATIC UTOPIA OF MARTHA NUSSBAUM - V. M. Karelin (Высшее образование в России)
The paper analyzes the conception of the development of education in the Humanities in the theory of the famous American philosopher Martha C. Nussbaum. According to her approach, modern education in the humanities on all the levels up to the university level must be based on skills of critical thinking. The “Socratic thinking” is represented as the basis for critical thinking as well as for development of modern democracy. This idea contains the confusion of notions and terms, thus assimilates Ancient Greek democracy and nowadays democracy, “humanities” and “humanism”; it is showed that such terms are not applicable to the conditions of modern society; all that leads to the conclusion on the utopian nature of the project.